1997
DOI: 10.1172/jci119652
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative responses to recall antigens are associated with pregnancy outcome in women with a history of recurrent spontaneous abortion.

Abstract: Maternal tolerance of the fetal hemiallograft suggests that immunomodulation occurs during gestation. Therefore, recurrent spontaneous abortion (RSA) may represent a failure of the immune changes that maintain pregnancy. We hypothesized that fertile women but not women with RSA may lose their immune responses to recall antigens when pregnant. This phenomenon has been seen in immunosuppressed transplant recipients and is associated with graft survival. Therefore, we evaluated proliferative responses to recall a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Among several explanations for the acceptance of the fetus, the one that suggests that the maternal immune system is suppressed or modified has been the subject of many studies. In agreement, several reports have demonstrated that during the normal pregnancy, a state of systemic suppression of the maternal immune system seems to be present . However, except for certain pathogens with defined predilection for prenatal infection, in general pregnant women are not significantly more susceptible to infections than non‐pregnant …”
Section: Introductionsupporting
confidence: 82%
“…Among several explanations for the acceptance of the fetus, the one that suggests that the maternal immune system is suppressed or modified has been the subject of many studies. In agreement, several reports have demonstrated that during the normal pregnancy, a state of systemic suppression of the maternal immune system seems to be present . However, except for certain pathogens with defined predilection for prenatal infection, in general pregnant women are not significantly more susceptible to infections than non‐pregnant …”
Section: Introductionsupporting
confidence: 82%
“…These peripheral and local changes could be the result of the direct action of progesterone on peripheral and uNK cells through nongenomic pathways or indirect effects on NK cells through support of a Th2 cytokine environment. It is known that proliferative responses of PBMC to recall antigens such as influenza A and tetanus as well as to alloantigens are significantly decreased in healthy women in early pregnancy compared with the nonpregnant state (159). These changes occur in an immune environment characterized by decreased levels of Th1 cytokines.…”
Section: A Model Of Nk Cell Function In Pregnancy Vs Rplmentioning
confidence: 99%
“…There is evidence both in murine and human studies that during pregnancy the maternal immune response is of the Th2 type, as Th1 type cell mediated immune responses are potentially harmful to the maintenance of pregnancy 65-68. Pregnant women have compromised cell mediated immunity,69 impaired lymphocyte proliferation,70 and loss of peripheral blood mononuclear cell (PBMC) proliferative responses to recall antigens 71…”
Section: Maternal-fetal Immunological Interactions and Childhood Asthmamentioning
confidence: 99%